Modelo de negocio para el uso de cápsulas tecnológicas, ideales para caninos en la ciudad de Bogotá. (2021)
This scientific article presents an alternative for those who want to include their pets in their shopping trips. Consequently, by means of a detailed analysis, an enormous difficulty is evident in terms of the limited spaces for pets in places such as chain stores. For this reason, a study of the internal and external impacts that affect the organization is carried out.